The Correlation between Students’ Interest in Game Activities and Their Vocabulary Mastery of the Fourth Semester at English Education Department of UIN SUSKA Riau - M. Ridho Al-Hafiz; Nurdiana Nurdiana; Afrizal Afrizal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACT. The purpose of this research is to examine whether there is any significant correlation between students’ interest in game activities and their vocabulary mastery of the Fourth semester at English Education Department of UIN SUSKA Riau. There were 28 students as samples by using simple random sampling technique. This research approach was quantitative method and the technique used in this research was a correlational technique. In collecting the data, the researcher distributed questionnaire and test to the respondents. To determine the students’ interest in game activities, the researcher used questionnaire which consist of 17 and used vocabulary mastery test which consist of 23 items to measure students’ vocabulary mastery. The researcher used Pearson product moment through SPSS 22.0 to analyze the data. The result of this research showed that sig. r obtained value is 0.907 higher than alpha value (0.05). It means that null hypothesis (Ho) is accepted while alternative hypothesis (Ha) is rejected. The value of r obtained is -0.023 < r table 0.374. In conclusion, there is no correlation between students’ interest in game activities and their vocabulary mastery of the Fourth semester at English Education Department of UIN SUSKA Riau.Key words: Students’ Interest in Game Activities, Vocabulary Mastery.